Translation as (Mis)interpretation: The Case of the Philosophy of the Late Fichte - Іван Іващенко (Філософія освіти)
The article examines the essays dedicated to the philosophy of the late Fichte, specifically to the concept of the image and the absolute (Netrebiak, 2022 and 2024). It demonstrates the issues arising, on the one hand, from neglecting the context of Fichte’s philosophy in attempts to interpret his late philosophy and, on the other hand, from misinterpreting Fichte’s terminology and incorrect translations of his texts. Additionally, it refutes the claim regarding the theological context of Fichte’s philosophy, which consistently developed Kant’s program of transcendental philosophy. This program aimed at reforming Christian epistemology and ethics by considering knowledge as the source of faith. The article also deals with Kant’s thesis on the setting aside (aufheben) of knowledge in order to make room for faith (KrV, B XXX) in the context of Luther’s translation of the biblical verb καταργεῖν (Rom. 3:31) as Kant’s claim for a reformation of Christianity. The path of Christianity (and the Christian philosopher) is the justification of knowledge (law, norms) through faith. Kant, however, radically rethinks this stance by justifying faith through knowledge. At bottom, Kant revises Christianity by rejecting transcendence, the supposed source of epistemic and practical world relations, leading to his critique of Christian ethics and its golden rule of morality whithin his doctrine of categorical imperatives. From this perspective, Fichte merely continues Kant’s program of transcendental philosophy, offering a path from knowledge to faith. Attempts to put forward a theological interpretation of Fichte’s Wissenschaftslehre fundamentally contradict both the early and later versions of the Wissenschaftslehre, as they disregard the epistemological context in which Fichte consistently developed Kant’s revolutionary equating of objective validity with objective reality, even though he employed his own original theoretical vocabulary.